Present-day changes in the morphology of the shore zone in the conditions of heavy tourist use: the case of Lake Czarne (upper Parsęta catchment) - Cichoń, Małgorzata (Quaestiones Geographicae, 2011)
So far, works on the effect of tourist use on relief have usually focused on mountain areas. Research confirms that changes in montane geoecosystems are not always a natural manifestation of landscape evolution, but often result from poorer resistance to degradation caused by heavy tourist traffic. In spite of a great number of studies concerning this problem, few address the effect of tourists on the geographical environment of lake-land areas. Hence, Lake Czarne was selected to determine the dynamics of morphogenetic changes in its shore area, especially in the scarp zone, with the help of geodetic surveys and studies of tourist capacity conducted in the years 2006-2009. On the basis of observations and the research, four stages in the evolution of the shore zone of Lake Czarne were distinguished that were correlated with specific meteorological and hydrological conditions affecting the number of recreationists on the beach.